Pengaturan Perubahan Fungsi pada Kawasan Perumahan Konservasi: Studi Kasus Kawasan Konservasi Cisangkuy, Bandung - Michael Isnaeni Djimantoro (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Human life is more complex with more and diverse human activities, requires an adjustment function on an area of the city. City areas will be abandoned later died at a city area with many buildings that are not maintained anymore. Therefore it needs adjustment function, a function of the new requirement is necessary to maintain the vitality of an area. This principle applies generally to the entire region, including the old town conservation area. Many examples of successful for the revitalization of old town that is how the old town area can adapt to the needs of the new society. Cisangkuy area is part of the initial planning of Bandung city, which is planned as a residential area for officials Dutch East Indies. Current conditions, the region has experienced a change to suit the needs of society. On the other hand, this region also have the value - historical value can still be inherited by future generations. Therefore, the necessary arrangements for the changes that occur to meet the needs of today's society does not damage the characteristics of the region as a whole.